A Consumption v. Savings Analysis of Increasing the Superannuation Guarantee Levy. Issue 1 (10th December 2019) - Evans, John R.; Razeed, Abdul
Abstract : The Superannuation Guarantee Levy (SGL) is scheduled to be increased from 2025, and there is evidence that an increase could be offset against wages. This paper uses a dynamic model to estimate the distribution of the impact of the SGL increase on both pre‐ and post‐retirement standards of living. The paper shows the increase in the SGL rate has the potential to reduce current consumption for the mean household below the "first level of financial stress" (derived from ABS (6530) Table 11.4) whilst only marginally increasing post‐retirement consumption. The SGL increase may not be an acceptable trade‐off between current consumption and retirement savings.